RESPONSIBLE MANAGEMENT AND SUSTAINABLE HUMAN REINTEGRATION - Conrado, Fernanda Caroline; Calbusch, Kevin Gonçalves; Lopes, Rafael Ávila; Broering, Geovani; Rodrigues, Renato (Seven Editora, 2026)
The homeless population represents one of the most complex social phenomena in contemporary societies, resulting from structural processes of social exclusion, economic inequality and the weakening of family and community ties. This article analyzes the Lages Recupera Program, a municipal public policy aimed at sheltering, assisted transition and socioeconomic reintegration of the homeless population in the city of Lages, Santa Catarina, Brazil. The study adopts a qualitative approach based on literature review, normative analysis and a case study of a municipal public policy. The theoretical framework incorporates contributions from Lenio Streck, Pedro Serrano, Paulo Freire, Moacir Gadotti, José Carlos Libâneo, Selma Garrido Pimenta and Slavoj Žižek, as well as institutional data from IBGE and IPEA. The findings indicate that integrated public policies combining assisted housing, psychosocial support, professional training and productive inclusion have greater potential to reduce homelessness and promote human dignity. The study concludes that the Lages Recupera Program represents an important instrument for sustainable human development aligned with the Brazilian Constitution of 1988, human rights principles and the Sustainable Development Goals of the United Nations 2030 Agenda.